Privacy Of Jurisdiction - Faraj, Amina; Abdel-Sahib, Ali (Journal of Legal Sciences, 2023)
The right of jurisdiction is one of the legal systems related to the guarantee, which aims to give the creditor a position that favors him over other creditors. Jurisdiction in bona fide is a consequential real right over the real estate subject of jurisdiction, enabling him to collect his right ahead of all other ordinary creditors and owners of ancillary real rights, from the price of the real estate or any money that replaces it, and in whatever hands it is. The right of jurisdiction, like the ancillary rights in rem, provides confidence to the creditor through his jurisdiction with a special guarantee that encourages him to grant credit to the debtor, by giving him a sufficient period for fulfillment, which is reflected in the increase in trade exchange and the prosperity of financial transactions in general.